What Explains the Pattern of Fibrosis in Chronic Graft‐Versus‐Host Disease? - Mohammadamin Noorafrooz; Hoda Kavosi; Robert Peter Gale (Clinical Transplantation, 2026)
ABSTRACT Fibrosis is common in diverse conditions but has different patterns across tissues and organs despite shared cellular and molecular pathways reasons for which are mostly unexplained. In this review we discuss chronic graft‐Versus‐host disease (G v HD), progressive systemic sclerosis (PSS), idiopathic pulmonary fibrosis (IPF), primary myelofibrosis (PMF), chronic lung allograft dysfunction (CLAD) and VEXAS syndrome to explore potential mechanisms underlying these patterns of fibrosis. We propose the distribution of fibrosis reflects a complex interplay between aetiology, initiating stimuli, local immune response, tissue‐specific micro‐environment and host susceptibility. Distinguishing systemic and local drivers of fibrosis is needed to understand and explain these patterns. A deeper understanding of early, tissue‐specific events governing fibrotic responses may allow development of preventive and therapeutic strategies.